Experimental investigation of Al5052‐H32/PETG hybrid clinched joints. Issue 21 (10th February 2022) - Ouyang, Yawen; Chen, Chao; Ren, Xiaoqiang; Ran, Xiangkun
Abstract: The mechanical clinching technique with an extensible die is selected to connect the metal‐polymer hybrid structure in this article. Al5052‐H32 is chosen as the metallic material. Polyethylene terephthalate glycol (PETG) was chosen as the polymer material. The connection between Al5052‐H32 and PETG is accomplished under diverse forming forces. To evaluate the joinability of hybrid joints, the dimension parameters of hybrid joints are measured by inspecting the transverse section of clinched joints. To evaluate the reliability of joints, the tensile shear test and the energy absorption calculation are accomplished. Moreover, the effect of various forming forces on the mechanical characteristics and failure mode of the hybrid structure is analyzed. The results showed that the Al5052‐H32 sheet and PETG sheet could be effectively connected. The optimal forming force is 38 kN in this experiment. Under this condition, the maximum tensile shear load and the maximum energy absorption value are 1520.16 N and 4.69 J, respectively. Abstract :